1994
DOI: 10.1063/1.111428
|View full text |Cite
|
Sign up to set email alerts
|

Highly tetrahedral, diamond-like amorphous hydrogenated carbon prepared from a plasma beam source

Abstract: Articles you may be interested inHydrogen stability in hydrogenated amorphous carbon films with polymer-like and diamond-like structure J. Appl. Phys. 112, 093502 (2012); 10.1063/1.4764001Pulsed laser deposition of hydrogenated amorphous diamondlike carbon films from a polymer target Formation of electrically conductive nitrogendoped amorphous hydrogenated carbon (diamondlike carbon) films by the supermagnetron plasma chemical vapor deposition method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 168 publications
(76 citation statements)
references
References 23 publications
7
67
0
2
Order By: Relevance
“…A peak in both the sp 3 fraction as well as the density is observed at an ion energy of 88 eV. Peaks in the density versus ion energy curve seem to be system dependent for different research groups and have been observed at; 40, 92, 140, and a threshold value of 50 eV in the results of McKenzie, 15 Weiler, 9 Fallon, 2 and Lifshitz, 16 respectively. The films deposited in the current work 17 use a similar apparatus to those used by McKenzie 15 and Fallon 2 .…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…A peak in both the sp 3 fraction as well as the density is observed at an ion energy of 88 eV. Peaks in the density versus ion energy curve seem to be system dependent for different research groups and have been observed at; 40, 92, 140, and a threshold value of 50 eV in the results of McKenzie, 15 Weiler, 9 Fallon, 2 and Lifshitz, 16 respectively. The films deposited in the current work 17 use a similar apparatus to those used by McKenzie 15 and Fallon 2 .…”
mentioning
confidence: 64%
“…9 There is much interest in all of these films due to their unique mechanical properties. 7,10 Recently, Yin et al 11 have found cauliflower-like growths ͑nanocrys-tals͒ which cannot be indexed to graphite in their FCVA deposited films, which are considered to be precursors for diamond growth.…”
mentioning
confidence: 99%
“…The PBS apparatus is similar to that used by Weiler et al 13 in which the structure of the a-C:H film is controlled solely by ions. A radio frequency ͑rf͒ power of 30 W at 13.56 MHz is applied via a capacitor and matching network between the ground electrode and the powered electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Weiler et al 13 reported that it is possible to deposit amorphous hydrogenated carbon films with high sp 3 ͑75%͒ and H contents ͑27%͒, and stated 14 that it is possible to dope the ta-C:H films deposited using the plasma beam source ͑PBS͒. However, it should be noted that ta-C films 15 as well as a-C films deposited by PBS 14 possess defect densities as high as 1ϫ10 20 defects/cm 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation